2013
DOI: 10.1371/journal.pone.0059821
|View full text |Cite
|
Sign up to set email alerts
|

The Golgin Tether Giantin Regulates the Secretory Pathway by Controlling Stack Organization within Golgi Apparatus

Abstract: Golgins are coiled-coil proteins that play a key role in the regulation of Golgi architecture and function. Giantin, the largest golgin in mammals, forms a complex with p115, rab1, GM130, and soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), thereby facilitating vesicle tethering and fusion processes around the Golgi apparatus. Treatment with the microtubule destabilizing drug nocodazole transforms the Golgi ribbon into individual Golgi stacks. Here we show that siRNA-mediated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 32 publications
9
70
0
Order By: Relevance
“…As the staining pattern for MFSD14A revealed a more condensed intracellular localization, co-staining with intracellular organelle markers for Golgi was performed. Anti-Giantin antibody, targeting a protein located in the cisterna of the Golgi apparatus (Linstedt and Hauri, 1993; Koreishi et al, 2013), overlapped well with MFSD14A staining ( Figure 6B ). Since MFSD14B had a more spread out staining pattern, co-staining with an anti-KDEL antibody was performed.…”
Section: Resultsmentioning
confidence: 76%
“…As the staining pattern for MFSD14A revealed a more condensed intracellular localization, co-staining with intracellular organelle markers for Golgi was performed. Anti-Giantin antibody, targeting a protein located in the cisterna of the Golgi apparatus (Linstedt and Hauri, 1993; Koreishi et al, 2013), overlapped well with MFSD14A staining ( Figure 6B ). Since MFSD14B had a more spread out staining pattern, co-staining with an anti-KDEL antibody was performed.…”
Section: Resultsmentioning
confidence: 76%
“…This unique structure suggested that it might play a role in vesicle tethering to the Golgi membranes in conjunction with p115 and GM130, another p115-interacting golgin (Alvarez et al, 2001;Lesa et al, 2000;Linstedt et al, 2000;Sönnichsen et al, 1998). Whereas several other golgins, as well as p115, have been shown to be essential for Golgi structural integrity in siRNA knockdown studies in cell culture assays, knockdown of Golgb1 mRNAs or protein did not cause disruption of Golgi structures or reassembly following mitosis (Koreishi et al, 2013;Puthenveedu and Linstedt, 2001). Recently, Kim et al generated mice heterozygous for Uso1, encoding the p115 protein, and confirmed genetically that p115 function is required for Golgi structural integrity and cell survival (Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Golgb1 has been found to interact with the transcytosis-associated protein p115 (also known as Uso1), a cytosolic protein involved in tethering endoplasmic reticulum (ER)-derived vesicles to the Golgi in mammalian cells as well as in yeast (Cao et al, 1998;Koreishi et al, 2013;Puthenveedu and Linstedt, 2001). Mouse embryos deficient in p115 exhibit early embryonic lethality and Golgi fragmentation in trophoblast cells (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Giantin is a resident Golgi protein that is anchored to the membrane of Golgi. It forms a complex with other Golgi proteins, such as p115 and Rab1, and regulates vesicle tethering and fusion processes in the Golgi apparatus (44). We used Giantin-RLuc8 as a localization marker to examine PAR 2 -induced translocation of G␤␥ to the Golgi compartment.…”
Section: Pkd Mediates Par 2 Translocation From the Golgi Apparatus Tomentioning
confidence: 99%